2021
DOI: 10.1136/bmjopen-2020-047882
|View full text |Cite
|
Sign up to set email alerts
|

Association between surgeon grade and implant survival following hip and knee replacement: a systematic review and meta-analysis

Abstract: ObjectiveTo investigate the association between surgeon grade (trainee vs consultant) and implant survival following primary hip and knee replacement.DesignA systematic review and meta-analysis of observational studies.Data sourcesMEDLINE and Embase from inception to 6 October 2021.SettingUnits performing primary hip and/or knee replacements since 1990.ParticipantsAdult patients undergoing either a primary hip or knee replacement, predominantly for osteoarthritis.InterventionWhether the surgeon recorded as per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that the training grade does not influence the revision risk following primary TKA. 30 This study suggests that does not seem to be the case following revision surgery with a HKA and that a consultant grade surgeon should be involved in the surgery.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have shown that the training grade does not influence the revision risk following primary TKA. 30 This study suggests that does not seem to be the case following revision surgery with a HKA and that a consultant grade surgeon should be involved in the surgery.…”
Section: Discussionmentioning
confidence: 79%
“…The reason might be the patient's condition of the Trainee Surgeons were less complicated than the Consultant Surgeons. There was no evidence to prove that Trainees had worse postoperative outcomes than Consultants by comparing the survival years and revision rates in the existing literature 20 …”
Section: Discussionmentioning
confidence: 99%
“…There was no evidence to prove that Trainees had worse postoperative outcomes than Consultants by comparing the survival years and revision rates in the existing literature. 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation